A preliminary investigation to develop a semi-probabilistic model of informal settlement fire spread using B-RISK. (March 2021) - Cicione, Antonio; Wade, Colleen; Spearpoint, Michael; Gibson, Lesley; Walls, Richard; Rush, David
Abstract: In South Africa alone, there are more than 5000 informal settlement fires a year, where a single incident can leave up to 10000 people homeless. The government and local authorities of countries with informal settlements, that extend over large areas, have no tools to simulate fires to identify high risk areas, or to quantify the magnitude of an incident to which they may need to respond. It is with this backdrop that the paper seeks to develop a semi-probabilistic method to determine fire spread rates in informal settlements. Data from a full-scale fire experiment is used to validate the fire spread rates predicted by B-RISK from which a simplified semi-probabilistic analysis method is developed that can estimate fire spread rates in informal settlements. B-RISK simulations are then compared to an actual informal settlement fire incident to assess its predictive capabilities. The paper also discusses how the effect of wind has been included and what additional features could be incorporated to obtain more realistic informal settlement fire spread predictions. This work provides the first step in a complex problem where it is difficult to accurately define input parameters.